Low dietary quercetin intake by food frequency questionnaire analysis is not associated with hypertension occurrence. Issue 6 (June 2021) - Yao, Zhanxin; Dai, Kun; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Gu, Yeqing; Sun, Shaomei; Wang, Xing; Jia, Qiyu; Song, Kun; Li, Zhe; et al.
Summary: Background & aims: Quercetin is one of the most abundant flavonoids in plant kingdom. Because of its strong anti-inflammatory and antioxidant effect, it is of potential in anti-hypertension. The objective of the present study was to explore the relationship between dietary quercetin and hypertension incidence in a Chinese population. Methods: Participants aged 17–87 years were recruited at baseline. Those people who did not have hypertension, cardiovascular disease or cancer and finished physical checkup were included in this prospective cohort study. A food frequency questionnaire (FFQ) was performed. Follow-up was conducted once a year. The intake of quercetin was calculated based on FFQ and Chinese food composition table. Three Cox proportional hazard regression models were used to investigate the relationship between quercetin intake and incidence of hypertension. Results: The data of 15, 662 participants, including 7340 males and 8322 females, were analyzed. The median follow-up period was 3.0 year and the follow-up rate is 85.2%. A total of 2463 subjects developed hypertension during the follow-up period. The mean of daily quercetin intake was 24.7 ± 13.8 mg/day in this population. In the multivariate adjusted Cox proportional hazard regression model, the hazard ratios (95% CI) for hypertension across the ascending quartiles of quercetin intake were: 1.00 (reference), 1.04 (0.92, 1.17), 0.99 (0.87, 1.12), and 1.06 (0.92, 1.21). No significant association was observed between quercetin intake and the incidence of hypertension. Conclusion: The dietary intake of quercetin alone does not reach a level sufficient to affect the incidence of hypertension in Chinese population.